Is myocardial revascularization really necessary in patients with ≥50% but <70% coronary stenosis undergoing valvular surgery?. (18th March 2020) - Del Forno, Benedetto; Ascione, Guido; Lapenna, Elisabetta; Trumello, Cinzia; Ruggeri, Stefania; Belluschi, Igor; Verzini, Alessandro; Iaci, Giuseppe; Ferrara, David; Schiavi, Davide; Meneghin, Roberta; Castiglioni, Alessandro; et al.
Abstract: OBJECTIVES: The aim of this study is to evaluate the immediate and mid-term effects of omitting coronary artery bypass grafting in patients with moderate coronary artery stenosis who have a primary indication for valvular surgery. METHODS: We included 77 consecutive patients admitted to our Institution for aortic or mitral valve surgery between June 2012 and June 2017 in whom a de novo diagnosis of ≥50%, but <70% coronary stenosis was made. In this cohort, the myocardial revascularization was omitted. All these patients were free from angina and ischaemia on echo and ECG. RESULTS: There were no in-hospital deaths. In only 1 patient, acute myocardial infarction occurred postoperatively, which was immediately treated by percutaneous coronary intervention (PCI). The 6-year overall survival was 94.7 ± 2.59%. At 6 years, no cardiac deaths were recorded. At follow-up, 4 patients underwent elective PCI after a positive stress myocardial perfusion test. Only 1 patient underwent urgent PCI due to acute coronary syndrome. At 6 years, the cumulative incidence function of PCI, with death as competing risk, was 8 ± 3.9%. CONCLUSIONS: In our experience, moderate coronary stenosis, occasionally discovered at the time of valvular heart surgery, can be safely overlooked and do not need any further treatment at follow-up in the majority of cases. Our results open up the opportunity to apply this 'intentional omission strategy' in different situations, such as minimally invasive heart surgery, percutaneous procedures and complex patients.